Peripheral mitochondrial transplantation alleviates diabetes-associated cognitive dysfunction by suppressing cuproptosis - Juan Hu; Qiao Li; Shiqiu Jiang; Yingying Deng; Lan Yang; Mengyu Du; Shuxuan He; Fuxing Xu; Chaoying Yan; Wei Gao; Yansong Li; Yaomin Zhu (Brain Research Bulletin)
Mitochondrial dysfunction and neuronal impairment are hallmark features of Diabetes-Associated Cognitive Dysfunction (DACD), mitochondrial transplantation is also a therapeutic intervention for DACD. However, the precise mechanism underlying its therapeutic effects are not fully elucidated. Given that imbalances in copper homeostasis and cuproptosis are associated with various neurodegenerative disorders and diabetic myocardial damage, we hypothesize a role for cuproptosis in the pathogenesis of DACD. We further propose that therapeutic peripheral mitochondrial transplantation may ameliorate DACD by reducing processes of cuproptosis. In this research, the study delved into the expression levels of cuproptosis-associated proteins FDX1, LIAS, and DLAT, as well as the copper content in both type 2 diabetes mellitus (T2DM) mice and primary neuronal cells exposed to high glucose and palmitic acid (HG/Pal). Furthermore, the cognitive capabilities of the mice were evaluated using a series of behavioral tests. The findings revealed that in primary neurons exposed to HG/Pal, the expression of copper levels was elevated, and the levels of FDX1, LIAS, and DLAT were reduced. Post-transplantation of platelet-derived mitochondria (Mito-Plt), a significant reversal of these biomarkers was noted, coincident with an improvement in cognitive deficits in T2DM mice. Significantly, the cuproptosis agonist elesclomol (ES) aggravated these alterations. In summary, the findings collectively suggest a causal connection between DACD and the development of cuproptosis in neurons. The use of exogenous Mito-Plt presents a promising therapeutic approach, capable of rescuing neurons from cuproptosis and thereby potentially alleviating DACD.